CNCB and Covid-19 pandemic: impacts on youth and adults school of Ceará (Research, Society and Development, 2021)
This work intended to analyze how the pedagogical politic project (PPP), school regiment and curriculum of public school in Ceará, Brazil, were affected by both Covid-19 and the guidelines of the new Common National Curriculum Bases (CNCB) to teaching of mathematics. Thereby, made up a bibliographic study about themes like: PPP and  school regiment and their importance for school administration; the impact of Covid-19 in schools; CNCB guidelines and impacts for education and for teaching of mathematics associated with the case investigation of youth and adults education center Jose Walter by document analysis of: PPP, school regiment; pedagogical guidelines from Ceará secretary of education and State Council of Education of Ceará to deploy the CNCB and to coordinate school actions during the pandemic scenario. The data revealed that both events provided: the development of a curriculum based in skills and abilities; integration of technologies to the curriculum, by a remote teaching and the possibility of development of hybrid teaching.